An Empirical Study of Service Recovery with Perceived Justice Impact on Customer Loyalty: A Pakistan’s Commercial Aviation Industry Perspective - Farooq Khurram (UW Journal of Management Sciences, 2021)
Purpose: The objective of the study is to analyze the effect of service recovery by applying the three dimensions of perceived justice (Justice Theory). Also, the mediating role of co-creating service recovery and moderation of culture was applied and measured. This study complements the prior literature by the mediating role of co-creation and moderation of culture. Design and Methodology: The population of the study is the passengers of the metropolitan city (Rawalpindi/Islamabad) of Pakistan who faced any service failure from Pakistan’s commercial airline. Data is gathered through a structured questionnaire from 357 respondents and a convenience sampling technique is used to gather the data. SPSS 20.0 is used for analysis. Findings: The findings of the study confirmed the previous studies and all three dimensions of perceived justice i.e., procedural, interactional, and distributive justice showed a positive relationship with customer loyalty with the mediating role of co-creation of service recovery. The interactional justice dimension strengthened the relationship more positively while the other two dimensions i.e., informational and distributive justice didn’t show a significant impact on customer loyalty when moderated by culture. Implications: Co-creation of service recovery is recommended for Pakistan’s airline industry with a large focus on interactional justice i.e., empathy, apology, and problem-solving behavior while interacting with the customers who faced the service failure.